Status Evaluation of Palm Oil Waste Management Sustainability in Malaysia - Aja, Aja; Oseghale, S.; Mohamed, A. (2017)
Malaysia occupies a strategic position in palm oil production and export in the world. The palm oil industrial process is been characterized by huge waste generation both in the upstream and downstream sectors. In 2015, the solid biomass waste generated in the palm oil industry in Malaysia was rated about 75.61 million tons per annum while the palm oil mill effluent (POME) waste generated amounts to 65.35 million tons per year. The palm oil biomass waste and POME generation are projected at 85-110 million tons and 70-110 million tons per year by 2020. The growth in the waste generation poses environmental sustainability challenges in relation to the waste management and greenhouse gas generation from both the solid biomass and POME. The status of the palm oil waste management is important considering sustainability in the industry and the environment, thus this study is centred on analysing the different waste management processes and their input in waste reduction and sustainability. This study is conducted using statistical data from the Malaysian Palm Oil Board and secondary data from literatures. It was observed that the Malaysian Palm oil industry is fast growing and currently has a plantation of over 5.74 million hectares where about 87% are mature palm trees which contributes to the high volume of solid waste through pruning. The management of the solid waste has been mainly the use of the wastes as bio-fertilizer like mulching and composting. Researches and technological development on the conversion of the waste to energy like in the heat and power is fully developed where the palm oil mills generate about 300MW of electricity while targeting 800MW by 2020. Other conversion processes of the solid waste to renewable energy in the form of biofuels (gasification, and briquette production) are in their different developmental stages. Palm oil solid waste has also been useful as bio-composite materials like the production of plywood/particle boards, fibre-mats, bio-char and activated carbon. Similarly, bio-chemical conversions have been employed in the management of palm oil solid waste which include extraction of sugars/cellulose, lignin, vitamin E, and carotenes which are currently at the emerging stage. The conversion of the POME fermentation product (Methane)/biogas is still in a very early stage in Malaysia even though methane has high negative impact on the environment. The management of the palm oil mills effluent is one major area where the Malaysia palm oil industry is still lagging behind. Out of the 450 palm oil mills in the country, only 90 mills representing 20% has installed biogas capturing system. Currently, 360 palm oil mills representing 80% of the total palm oil mills treat their generated POME in open ponding, 52 mills representing 12% uses Digester Tank while 38 mills (8%) treat the POME in Covered Lagoon. The analysis of the 90 mills that are involved in biogas capture showed that 52 mills flare the captured gas while 12 mills use the gas for Combined Heat & Power generation, 24 mills use the gas for electricity generation, while 2 mills use the gas for package boiler. It was also found that out of the 24 mills that generates electricity; 19 are connected to the grid while the others are mainly for the mills activities. It can be concluded that there is progress in the growth of sustainability in the Malaysia palm oil industry. More monitoring and applications of the research findings in the industry are required for faster growth in sustainability in the industry.